SARS-CoV-2-Induced Immunosuppression: A Molecular Mimicry Syndrome - Kanduc, Darja (Global Medical Genetics, 2022)
Background Contrary to immunological expectations, decay of adaptive responses against severe acute respiratory syndrome-coronavirus-2 (SARS-CoV-2) characterizes recovered patients compared with patients who had a severe disease course or died following SARS-CoV-2 infection. This raises the question of the causes of the virus-induced immune immunosuppression. Searching for molecular link(s) between SARS-CoV-2 immunization and the decay of the adaptive immune responses, SARS-CoV-2 proteome was analyzed for molecular mimicry with human proteins related to immunodeficiency. The aim was to verify the possibility of cross-reactions capable of destroying the adaptive immune response triggered by SARS-CoV-2.Materials and Methods Human immunodeficiency–related proteins were collected from UniProt database and analyzed for sharing of minimal immune determinants with the SARS-CoV-2 proteome.Results Molecular mimicry and consequent potential cross-reactivity exist between SARS-CoV-2 proteome and human immunoregulatory proteins such as nuclear factor kappa B (NFKB), and variable diversity joining V(D)J recombination-activating gene (RAG).Conclusion The data (1) support molecular mimicry and the associated potential cross-reactivity as a mechanism that can underlie self-reactivity against proteins involved in B- and T-cells activation/development, and (2) suggest that the extent of the immunosuppression is dictated by the extent of the immune responses themselves. The higher the titer of the immune responses triggered by SARS-CoV-2 immunization, the more severe can be the cross-reactions against the human immunodeficiency–related proteins, the more severe the immunosuppression. Hence, SARS-CoV-2-induced immunosuppression can be defined as a molecular mimicry syndrome. Clinically, the data imply that booster doses of SARS-CoV-2 vaccines may have opposite results to those expected.
Keywords: SARS-CoV-2; immunosuppression; molecular mimicry; cross-reactivity; NFKB; V(D)J RAG proteins